Development and initial validation of the Interaction Anxiety in Group Work (IAGWS) Scale - Xethakis, Larry J.; Rupp, Michael; Plummer, Brendan R. B.; Kawagoe, Toshikazu (Frontiers in Education, 2025)
IntroductionSocial interaction, especially in small groups, has become a widely used teaching methodology in the language classroom and can provide learners with a wide range of benefits. It can also place cognitive and affective demands on learners, provoking feelings of social anxiety, which can become an obstacle to learning. However, there is a lack of scales to measure social anxiety as it operates in small group work. The aim of this study was to develop and evaluate the psychometric properties of a short measure of interactional anxiety, the Interaction Anxiety in Group Work Scale (IAGWS), grounded in the self-presentation theory of social anxiety.MethodsThe study followed a four-phase development process: (1) item development followed by content validity assessment by experts and English learners; (2) item assessment and exploratory factor analysis to determine dimensionality; (3) the structure was tested using confirmatory analysis, and construct validity and reliability were determined; (4) concurrent validity was assessed through correlation analysis with related scales, and temporal reliability was measured.ResultsThe final scale comprised 11 items with three dimensions: Becoming the Center of Attention (6 items), Working with New People (2 items), and Coping with Ambiguous Situations (3 items). The goodness-of-fit indices (χ2 = 221.379, p < 0.001; TLI = 0.966; CFI = 0.975; RMSEA = 0.077; SRMR = 0.028). AVE values ranged from 0.682 to 0.745. CR ranged from 0.865 to 0.946, omega from 0.871 to 0.953, and alpha from 0.871 to 0.954. Scores on the IAGWS exhibited significant, positive correlations with scores on each criterion instrument. ICC values for temporal reliability were all above 0.8.DiscussionThe IAGWS has been shown to be a reliable and validate measure of interaction anxiety. It can be used in research on the impact of social anxiety on group work, as well as the effectiveness of interventions aimed at reducing the detrimental influence of anxiety.